Is the relationship between innovation performance and knowledge management contingent on environmental dynamism and learning capability? Evidence from a turbulent market - Rifat Kamasak; Meltem Yavuz; Gultekin Altuntas (Business Research, 2016)
This study aims to explore the separate and combined effects of knowledge management capabilities, environmental dynamism and learning capability on innovation performance. To achieve this aim, a survey was carried out on a sample of 221 firms and a couple of hypotheses were tested. The findings showed that higher levels of environmental dynamism and learning capability made the positive linkage between knowledge management capabilities and innovation performance stronger. Based on the findings, it was suggested that whilst environmental dynamism may compel firms to assimilate and use new information better, create more new product configurations and move readily to new markets through their knowledge management capabilities, learning capability improves the understanding of organizational knowledge and helps the firm embed this knowledge into organizational processes. In this sense, environmental dynamism and learning capability moderate the relationship between knowledge management capabilities and innovation performance.
Keywords: L1; M19; 650; Environmental dynamism; Knowledge management; Learning capability; Emerging markets; Regression analysis; Turkey